Pro-environmental behavior and bioeconomy: Reflections on single-bottled water consumption - Iuliana Raluca Gheorghe; Victor Lorin Purcărea; Consuela Mădălina Gheorghe (Amfiteatru Economic Journal, 2019)
Nowadays, many global challenges such as climate change, food security, health, industrial restructuring, and energy conservation may be solved by applying the principles of bioeconomy. Adequately implementing the principles of Bioeconomy ensures a transition from a fossil-based economy to a bio-based economy. Although in most European countries, there is clean, safe and reliable drinking water, the bottled water industry has the fastest growing rate with severe consequences for the environment. This research assesses the intentions of Romanian university students regarding single-bottled water usage by implementing a pro-environmental behavior model. As such, this study extends the existing literature on pro-environmental behavior by identifying the factors specific to the single-bottled water consumption. The model encompassed the following factors which would influence the bottled water consumption: safety and hygiene, personal benefit, locus of control, personal responsibility, health benefits, environmental concerns, knowledge of action strategies and intention to adopt a pro-environmental behavior. Using Structural Equation Modeling, we validated the pro-environmental single-bottled water consumption model on a sample of 283 university students, with the mean age of 20. The nonprobabilistic sampling method was homogenous convenience type, nonrepresentative but with the possibility to determine an ideal defined group. The findings revealed that the primary motivation of the respondents to use bottled water was safety and hygiene and they would engage in a pro-environmental behavior in using refillable bottles for drinking water. Further, the study outlined the main implications for both theory and practice.
Keywords: Q01; Q02; Q25; Q53; Q57; 330; Bioeconomy; bottled water; pro-environmental behaviour; Bootsrapping method; Partial Least Squares